Intraoperative cell salvage as an effective intervention for postpartum hemorrhage—Evidence from a prospective randomized controlled trial - Lei, Bo; Guo, Min; Deng, Xin; He, Shujun; Lu, Xin; Wang, Yunjuan; Wang, Lei (Frontiers in Immunology, 2022)
Background: Postpartum hemorrhage (PPH) is one of leading causes of maternal mortality. Promptly recovering blood loss is critical for PPH. Intraoperative cell salvage (ICS) is a method to collect and process red blood cells from the blood lost during surgery and transfuse them to patient’s circulation during or immediately after surgery. Its effectiveness in reducing the demand of allogeneic blood transfusion has been proved, but its effectiveness and safety as a sole treatment for PPH during caesarean sections is unclear. This is particularly important for patients who cannot or don’t want to accept allogeneic blood transfusion. Materials and Methods: In this prospective randomized control study, patients with high risks of PPH were randomized into the ICS group or the control group, receiving ICS or allogeneic red blood cells (RBC) transfusion if their hemoglobin level was less than 80 g/L during operation. Data collected include clinical examination, blood cell count, hemoglobin level, coagulation function; plasma levels of fetal hemoglobin, tissue factor, and alpha-fetoprotein before and after fetal delivery, at 0, 2 and 12 hours after treatment. Adverse events were recorded. Results: A total of 130 patients were enrolled, aged 33±1 years with a mean gestation period of 37±1 weeks. The most common cause of caesarean section was placenta previa, followed by twin pregnancy, scarred uterus, preeclampsia, placental abruption, fetal distress and placenta accrete spectrum. Bleeding amount was similar between the two groups. The ICS group, compared to controls, had more efficient increases in hemoglobin level, red blood cell count and hematocrit (all p<0.05). Coagulation function was maintained in the ICS group but reduced in controls 24 hours after transfusion, indicated by significantly reduced fibrinogen level and prolonged PT, TT and APTT (all p<0.05). There was a transient but significant decrease in plasma tissue factor and alpha-fetoprotein levels and increase in plasma fetal hemoglobin level with ICS treatment in postpartum period. No adverse event occurred with ICS intervention. Conclusion: ICS is an effective and safe intervention for patients with high risk of PPH during selective or emergency caesarean section. It can effectively clear tissue factors and alpha-fetoprotein but not fetal hemoglobin.